Pengembangan diri dan soft skill: Pengaruh keaktifan ber-organisasi terhadap peningkatan kepercayaan diri & kemampuan komunikasi public mahasiswa - Sasmita, Zahra Herdinata (Maliki Interdisciplinary Journal, 2026)
In today’s era of globalization and digitalization, most students view joining campus organizations or academic programs as a waste of time that won’t yield clear personal benefits. And because of the heavy workload and time demands of these organizations, students are reluctant to join them. However, in the modern era and the reality of today’s job market, students are not only expected to excel academically but must also master essential soft skills such as self-confidence and public speaking ability, with the aim of enhancing their readiness for the workforce. Therefore, this study was conducted to explore how active involvement in student organizations contributes to the development of students’ character and public speaking skills. It employed a descriptive qualitative method with a phenomenological approach. The results indicate that organizations function as effective “social laboratories.” Participation in meetings, committee work, presenting ideas in forums, and advocacy efforts were found to significantly reduce anxiety about public speaking. Furthermore, the challenges and goals set by the organization help enhance students’ self-efficacy in decision-making and future interactions within the community.